Mouvement brownien et la relaxation des spins dans les systèmes moléculaires organiques - Rudolf Lenk (CHIMIA)
A survey is given of the possibility of applying the spin-proton relaxation method to the study of Brownian motion in organic substances. Brownian motion is represented by the Fokker-Planck equation and it is connected to the spin relaxation by means of the random modulation of dipole-dipole interaction. The cases of rotational and translation Brownian motions are discussed.